Prevalence and associated risk factors of bovine clinical mastitis in Patiya upazila under Chittagong district of Bangladesh - Bari, MS; Alam, M; Uddin, M; Rahman, MK (International Journal of Natural Sciences, 2016)
A cross sectional study was conducted to measure the prevalence; and identification of risk factors associated with clinical mastitis in dairy cows at Patiya upazila under Chittagong district of Bangladesh from 20th July to 31st December, 2013. A total of 160 farms and households were selected and 634 cows were clinically examined for determining the prevalence of mastitis and identification of risk factors. The overall prevalence of clinical mastitis was found 8.36%. Mastitis prevalence in crossbred cows was significantly (P<0.05) higher (10.09%) than indigenous cows (4.26%). The prevalence of mastitis was also significantly higher (P<0.05) with advancing age (12.5%) and in 3rd lactation period (13.62%). The cows were more prone to mastitis during 1st month of lactation (17.53%). There was a significant relationship (P<0.05) between prevalence of clinical mastitis and associated risk factors like general physical condition, herd size, frequency of dung removal, floor drainage quality and condition of floor. There was higher (P<0.01) prevalence (33.67%) of mastitis in cows having history of peri-parturient disease compared to those not having such history. Therefore, it can be concluded that minimization of risk factors of mastitis is very much necessary to control mastitis as well as to increase profitability of dairy farms. International Journal of Natural Sciences (2014), 4(1) 5-9